2002
DOI: 10.1159/000064950
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation for the Treatment of Chronic Pain – A Pilot Study

Abstract: Invasive electrical stimulation of the motor cortex has been reported to be of therapeutic value in pain control. We were interested whether noninvasive repetitive transcranial magnetic stimulation (rTMS) of the primary motor cortex might also act beneficially. Twelve patients with therapy-resistant chronic pain syndromes (mean age 51.3 ± 12.6, 6 males) were included in a pilot study. They were treated with rTMS of the corresponding motor cortex area for 20 min (20 Hz, 20 × 2 s trains, intensity 80% of motor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 16 publications
(20 reference statements)
2
55
0
9
Order By: Relevance
“…[65][66][67] Other energy therapies shown to have some benefit in both acute and chronic pain, e.g., repetitive transcranial magnetic stimulation, have also encountered difficulties in developing appropriate sham controls. [68][69][70][71][72] Physical modalities, such as chiropractic and massage, are equally difficult to blind, since the subjects under study can clearly discern whether they are truly receiving a massage or spinal manipulation. Furthermore, even a light touch can illicit changes in the limbic system, making it difficult to design a true control for physical modalities.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…[65][66][67] Other energy therapies shown to have some benefit in both acute and chronic pain, e.g., repetitive transcranial magnetic stimulation, have also encountered difficulties in developing appropriate sham controls. [68][69][70][71][72] Physical modalities, such as chiropractic and massage, are equally difficult to blind, since the subjects under study can clearly discern whether they are truly receiving a massage or spinal manipulation. Furthermore, even a light touch can illicit changes in the limbic system, making it difficult to design a true control for physical modalities.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Furthermore, since animals likely do not understand the difference between true vs sham therapies, we can infer that they are not likely to exhibit a placebo response. [71][72][73][74][75][76][77][78][79][80][81] Some argue that acupuncture is no better than placebo since a few human studies showed no significant difference between sham needling and true acupuncture-ignoring the effects of needle insertion itself. 82 Nevertheless, blinding attempts with non-penetrating shams are possible in humans.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…В трех исследо-ваниях (50 пациентов) при стимуляции зоны М1 была по-казана неэффективность высокочастотной рТМС [77,78,80]. Однако в этих работах использовалась круглая катуш-ка, которая не обеспечивает локального воздействия на стимулируемую зону [81]. В остальных исследованиях вы-сокочастотная рТМС была эффективна по сравнению с плацебо.…”
Section: болевые синдромыunclassified
“…TMS has the advantage of being noninvasive and safe if appropriate guidelines are followed [76] . Two recently published studies using rTMS applied to the motor cortex reported suppression of pain in patients with therapy-resistant chronic somatic pain syndromes [6,77] . In addition, Lefaucher et al [7] studied 60 patients suffering from intractable pain.…”
Section: Factors Determining Pain Response: Psychological and Geneticmentioning
confidence: 99%